Precipitating Factors for Acute Heart Failure Hospitalization and Long-Term Survival. Issue 52 (December 2015) - Berkovitch, Anat; Maor, Elad; Sabbag, Avi; Chernomordik, Fernando; Elis, Avishay; Arbel, Yaron; Goldenberg, Ilan; Grossman, Ehud; Klempfner, Robert
Abstract : Abstract: Heart failure (HF) patients have frequent exacerbations leading to high consumption of medical services and recurrent hospitalizations. Different precipitating factors have various effects on long-term survival. We investigated 2212 patients hospitalized with a diagnosis of either acute HF or acute exacerbation of chronic HF. Patients were divided into 2 primary precipitant groups: ischemic (N = 979 [46%]) and nonischemic (N = 1233 [54%]). The primary endpoint was all-cause mortality. Multivariate analysis demonstrated that the presence of a nonischemic precipitant was associated with a favorable in-hospital outcome (OR 0.64; CI 0.43–0.94), but with a significant increase in the risk of 10-year mortality (HR 1.12; CI 1.01–1.21). Consistently, the cumulative probability of 10-year mortality was significantly higher among patients with a nonischemic versus ischemic precipitant (83% vs 90%, respectively; Log-rank P value <0.001). Subgroup analysis showed that among the nonischemic precipitant, the presence of renal dysfunction and infection were both associated with poor short-term outcomes (OR 1.56, [ P < 0.001] and OR 1.35 [ P < 0.001], respectively), as well as long-term (HR 1.59 [ P < 0.001] and HR 1.24 [ P < 0.001], respectively). Identification of precipitating factors for acute HF hospitalization has important short- and long-term implications that can be used for improved risk stratification and management.